(untitled) (Global Journal of Science Frontier Research, 2021)
The article describes the research results obtained in the process of working out the flow path of modernized centrifugal pumps. The authors proposed the device of new elements based on the calculation of the flow limited only by the side walls. The purpose of this work is to change and clarify in the calculations of the economic indicators of the modes of pumping units and the features of the performance of modern low-pressure pumps. They are developed on the basis of the results of a large number of tests carried out by the authors of the pumping unit assemblies and operational surveys of irrigation pumping stations in Uzbekistan. Determination of the economically feasible duration of the operating period of pumping units, taking into account changes in energy characteristics and energysaving operating technologies, was clarified when measuring the efficiency of the modernized pump D2000-21 at various operating modes.